Learning environment in undergraduate institutes in Pakistan: Determining factors and suggestions - Jawaid, Masood; Aly, Syed Moyn (Journal of Postgraduate Medical Institute, 2014)
Learning environment is the sum of the internal and external circumstances and influences surrounding and affecting a person's learning. It comprises of everything that is happening in an undergraduate institution. It dependent upon each and everything in an educational organization like curriculum design, teaching methods, teachers' behavior with students', the atmosphere during teaching sessions, the social and academic environment and support system during stress This article attempts to discuss various aspects related to the learning environment including factors determining it, ways of evaluating it and suggestions for improving it in the context of Pakistan.